Exchange Rate Fluctuations and Economic Growth in Nigeria: An Empirical Analysis - Ozigbo, Sylvester Aigbogun; Ekane, Rapheal Ogagoghene; Ujuju, Lucky Ejieh (International Journal of Economics and Financial Issues, 2025)
This study investigates the relationship between exchange rate fluctuations and economic growth in Nigeria. Other specific objectives include: to find out the impact of inflation rate, interest rate and external reserve on growth of the economy. The ex-post facto research design technique was utilized. The data were obtained from the CBN Statistical Bulletin and Cointegration Error Correction Mechanism was adopted by analysing the data. The results obtained show that the exchange rate and interest rate were significant and negatively related to economic growth. Also, inflation rate and external reserve were significant but positively related to economic growth within the period covered by this study. It was therefore recommended that policy makers should not only rely on the manipulation of the macroeconomic variables to stem the tide of exchange rate fluctuations in the short run but go further to design policies that can bring about increase in production of goods and services in Nigeria. This will result in boosting the foreign exchange earnings that will ultimately improve the exchange rate of the local currency against other major currencies in the long run.